Global Patterns of Aquatic Macroinvertebrate Dispersal and Functional Feeding Traits in Aridland Rock Pools - Washko, Susan; Bogan, Michael T. (Frontiers in Environmental Science, 2019)
Rock pools are important desert ecosystems that provide rare sources of surface water in arid regions. Hydroperiod is one of the primary limiting factors on aquatic macroinvertebrates living in rock pools. Resident macroinvertebrates must complete their life cycles before drying, and may employ active or passive dispersal strategies to survive drying. Quantifying dispersal and functional feeding traits across rock pool macroinvertebrate communities in multiple regions could provide insight into how rock pool ecosystems will respond to shorter hydroperiods predicted by climate change models. Here, we analyze taxonomic data (26 species lists) obtained from 24 published studies of rock pools to assess the dispersal and feeding strategies of macroinvertebrates, and how ecosystem functions may change with shorter hydroperiods. On average across all data sets, taxa were equally comprised of active dispersers and passive dispersers. Most active disperser taxa were predators (60%) and gatherers (33%). In contrast, passive disperser taxa were generally filterers (39%), gatherers (29%), and scrapers (21%). Climate change scenarios may result in shorter rock pool hydroperiods in many regions, which could reduce habitat availability for passive dispersers with weak overland dispersal abilities. If passive disperser populations decrease, their associated ecosystem functions, such as fine organic matter processing, could be disrupted. These results provide a foundation for future work investigating changes in rock pool ecosystem function due to altered hydroperiods.